2021
DOI: 10.1002/tax.12511
|View full text |Cite
|
Sign up to set email alerts
|

A near comprehensive phylogenetic framework gives new insights toward a natural classification of the African genus Cyrtorchis (Angraecinae, Orchidaceae)

Abstract: The genus Cyrtorchis is renowned for its conspicuous white, long‐spurred flowers, but also for its challenging problems of species delimitation due to the great morphological resemblance of their flowers. Based on a preliminary visual inspection of 1752 specimens, 27 morphogroups were defined including 6 unpublished taxa. Then, we used a representative sampling of 171 dried and alcohol‐preserved specimens representing 20 morphogroups to perform linear morphometrics through multivariate analyses on 43 morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…A recent study combining morphological and molecular data on the African angraecoid genus Cyrtorchis tested the monophyly of its two sections and re-assessed the circumscription of each described species (Azandi et al 2021). This study revealed three novelties, and among these, one is endemic to the Cameroon Volcanic Line (CVL).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study combining morphological and molecular data on the African angraecoid genus Cyrtorchis tested the monophyly of its two sections and re-assessed the circumscription of each described species (Azandi et al 2021). This study revealed three novelties, and among these, one is endemic to the Cameroon Volcanic Line (CVL).…”
Section: Introductionmentioning
confidence: 99%